Activation of A2A Receptor by PDRN Reduces Neuronal Damage and Stimulates WNT/β-CATENIN Driven Neurogenesis in Spinal Cord Injury - Irrera, Natasha; Arcoraci, Vincenzo; Mannino, Federica; Vermiglio, Giovanna; Pallio, Giovanni; Minutoli, Letteria; Bagnato, Gianluca; Anastasi, Giuseppe Pio; Mazzon, Emanuela; Bramanti, Placido; Squadrito, Francesco; Altavilla, Domenica; et al. (Frontiers in Pharmacology, 2018)
Spinal cord injury (SCI) is a complex clinical and progressive condition characterized by neuronal loss, axonal destruction and demyelination. In the last few years, adenosine receptors have been studied as a target for many diseases, including neurodegenerative conditions. The aim of this study was to investigate the effects of an adenosine receptor agonist, PDRN, in an experimental model of SCI. Moreover, since adenosine receptors stimulation may also activate the Wnt pathway, we wanted to study PDRN effects on Wnt signaling following spinal cord injury. Spinal trauma was induced by extradural compression of spinal cord at T5-T8 level in C57BL6/J mice. Animals were randomly assigned to the following groups: Sham (n=10), SCI (n=14), SCI+PDRN (8 mg/kg/i.p.; n=14), SCI+PDRN+DMPX (8 mg/kg/i.p. and 10mg/kg/i.p. respectively; n=14). DMPX was used as an adenosine receptor antagonist to evaluate whether adenosine receptor block might prevent PDRN effects. PDRN systemically administered 1 hour following spinal cord injury, protected from tissue damage, demyelination, and reduced motor deficits evaluated after 10 days. PDRN also reduced the release of the pro-inflammatory cytokines TNF-α and IL-1b reduced BAX expression and preserved Bcl-2. Furthermore, PDRN stimulated Wnt/b-catenin pathway and decreased apoptotic process 24 hours following SCI, whereas DMPX administration prevented PDRN effects on Wnt/b-catenin signaling. These results confirm PDRN anti-inflammatory activity and demonstrate that a crosstalk between Wnt/-catenin signaling is possible by adenosine receptors activation. Moreover, these data let us hypothesize that PDRN might promote neural repair through axonal regeneration and/or neurogenesis.